MATERNAL AND FETAL HEPATIC INJURY IN GESTATIONAL DIABETIC RATS: PROTECTIVE ROLE OF CINNAMALDEHYDE AND ELLAGIC ACID - Abdul-hamid, Manal; Hosni, Ahmed A; Moneim, Adel Abdel; Moustafa, Nadia; Abdel-reheim, Eman S (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study aims to determine the protective effect of cinnamaldehyde (Ci) and ellagic acid (EA) on maternal and fetal hepatic injury caused by fatty-sucrosed-diet/streptozotocin (FSD/STZ)-rat model of gestational diabetes (GD). Methods: Female Wistar rats were allocated into four groups. Group I fed with a normal diet, while Groups II, III, and IV feds with FSD for 8 weeks (five pre-gestational and three gestational). One week before mating onward, Group III and IV administered daily oral dose of 20 mg/kg Ci or 50 mg/kg EA, respectively. At the 7th day of gestation, FSD-fed groups injected intraperitoneally with STZ (25 mg/kg b.wt.) to induce GD mellitus. At the end of gestation, maternal and fetal blood, pancreas and liver samples were taken for the subsequent analysis. Results: Ci and EA potentially protect from the elevated glucose, triglycerides, total cholesterols, liver transaminases, and the depleted serum insulin, high-density lipoprotein-cholesterol, total proteins and albumin of GD-rats. As well, tested agents alleviated the altered fetal glucose and insulin levels. Alongside, Ci and EA reduced the maternal and fetal liver lipid peroxidation and increased their total thiols and total peroxidases. Furthermore, Ci and EA kept the normal intact of maternal and fetal pancreatic islets and preserve their livers away from the pathological changes observed in GD group that included fatty depositions, inflammation, hepatocytic necrosis and fibrosis, congested veins, diminutive storable glycogen and proteins, and the numerous proliferating cell nuclear antigen nuclei. Conclusion: Ci and EA have potent hepatoprotective effects through their insulin-sensitizing action and activating the antioxidant defenses.